A Novel Creatinine Muscle Index Based on Creatinine Filtration: Associations with Frailty and Mortality. Issue 3 (26th March 2023) - Ballew, Shoshana H.; Zhou, Linda; Surapaneni, Aditya; Grams, Morgan E.; Windham, B. Gwen; Selvin, Elizabeth; Coresh, Josef; Miao, Shiyuan; Inker, Lesley A.; Levey, Andrew S.
Abstract : Significance Statement: Low muscle mass is related to frailty and increased mortality in older adults. However, muscle mass is not easily assessed in routine clinical practice. This paper describes a novel creatinine muscle index (CMI) on the basis of serum creatinine and cystatin C. CMI was moderately associated with frailty among older adults. A significantly higher proportion of individuals with weak grip strength were in the lowest tertile of CMI. The index was also associated with mortality. These results are consistent with the hypothesis that creatinine filtration may be an index of muscle mass, which may have utility in clinical practice. Background: Low muscle mass is related to frailty and increased mortality in older adults. However, muscle mass is not easily assessed in routine clinical practice. Methods: This study describes a novel creatinine muscle index (CMI) on the basis of serum creatinine and cystatin C in a community-based sample of older adults from the Atherosclerosis Risk in Communities Study. Analyses included 4639 participants who attended visit 5 (2011–2013) and 12, 786 participants who attended visit 2 (1990–1992). CMI was defined as creatinine filtration (the product of serum creatinine times eGFR on the basis of cystatin C) and was analyzed in sex-specific tertiles. Cross-sectional associations of CMI with a frailty trichotomy, defined by the number (robust [0]/prefrail [1–2]/frail [3–5]) of five frailty components (weight loss, slowness, exhaustion, weakness, and low physical activity), were studied using polychotomous logistic regression and binary logistic regression with each frailty component. Cox regression was used to estimate associations of CMI at visit 5 and visit 2 with mortality. Models were adjusted for demographics, clinical variables, and comorbid conditions. Results: CMI (tertile 1 versus 3) was moderately associated with frailty (visit 5: adjusted odds ratio 4.23 [95% confidence interval (CI), 2.02 to 8.87] in men and 2.34 [95% CI, 1.41 to 3.89] in women) and with mortality (visit 5: adjusted hazard ratio 1.45 [95% CI, 1.08 to 1.94] in men and 1.55 [95% CI, 1.13 to 2.12] in women; similar results were seen at visit 2). Conclusion: Lower CMI was associated with frailty and increased mortality, two clinical outcomes known to be associated with decreased muscle mass. Creatinine filtration may be an index of muscle mass and have utility in clinical practice, particularly at low levels.